Disaggregating Okun's law: A case-study for Macedonia - Danica Unevska Andonova; Magdalena Petrovska (National Bank of the Republic of Macedonia, 2018)
Okun's law is one of the most widely-known stylized facts in the macroeconomic literature and policy. In this paper, we study several aspects of Okun's law in Macedonia between 2004 and 2014. Aggregate indicators show a link between output and unemployment that is in line with this empirical regularity and the findings for the other emerging markets and regional peers. We also find that the relationship has been somewhat weaker in the recent years, which might be related to the recent job-intensive growth in the wake of structural reforms before and during the global financial crisis and particularly the subsequent European debt crisis. When investigating whether various expenditure components of GDP may cause different unemployment reactions, an important issue that has not been sufficiently addressed in the literature, we find that domestic demand has a stronger effect. We also provide several robustness checks to our main findings, and illustrate how they might be used to improve forecasting of unemployment.
Keywords: E2; E24; C22; 330; Okun's law; GDP; unemployment; Macedonia